2018
DOI: 10.1093/nar/gky924
|View full text |Cite
|
Sign up to set email alerts
|

Structural, functional and biological insights into the role ofMycobacterium tuberculosisVapBC11 toxin–antitoxin system: targeting a tRNase to tackle mycobacterial adaptation

Abstract: Toxin–antitoxin (TA) systems are involved in diverse physiological processes in prokaryotes, but their exact role in Mycobacterium tuberculosis (Mtb) virulence and in vivo stress adaptation has not been extensively studied. Here, we demonstrate that the VapBC11 TA module is essential for Mtb to establish infection in guinea pigs. RNA-sequencing revealed that overexpression of VapC11 toxin results in metabolic slowdown, suggesting that modulation of the growth rate is an essential strategy for in vivo survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 72 publications
3
48
0
Order By: Relevance
“…The transcript levels of esxK, esxL and hsdS.1 which were increased in the mutant strain were observed to be decreased in the overexpression strain. In agreement with earlier reports, transcript levels of non-cognate toxins and antitoxins such as vapC1, mazE3,vapB43,vapB22,vapC15,vapB17,Rv0366c,and vapB15 were also increased in the VapC21 overexpression strain ( Supplementary Table S3; Agarwal et al, 2018;Deep et al, 2018). DEGs annotated as regulatory proteins such as sigB, mce2R, whiB1, sigD, furA, whiB7, sigE, clgR were also upregulated in the overexpression strain ( Supplementary Table S3).…”
Section: Transcriptional Response To Vapc21 Overexpression In M Tubesupporting
confidence: 91%
See 3 more Smart Citations
“…The transcript levels of esxK, esxL and hsdS.1 which were increased in the mutant strain were observed to be decreased in the overexpression strain. In agreement with earlier reports, transcript levels of non-cognate toxins and antitoxins such as vapC1, mazE3,vapB43,vapB22,vapC15,vapB17,Rv0366c,and vapB15 were also increased in the VapC21 overexpression strain ( Supplementary Table S3; Agarwal et al, 2018;Deep et al, 2018). DEGs annotated as regulatory proteins such as sigB, mce2R, whiB1, sigD, furA, whiB7, sigE, clgR were also upregulated in the overexpression strain ( Supplementary Table S3).…”
Section: Transcriptional Response To Vapc21 Overexpression In M Tubesupporting
confidence: 91%
“…Several studies have shown that overexpression of toxins belonging to TA systems result in transcriptional reprogramming that might enable the bacteria to adapt to different stress conditions (Singh et al, 2010;Deep et al, 2018). We next performed RNA-seq analysis to compare the transcription profiles of parental and VapC21 overexpression strain.…”
Section: Transcriptional Response To Vapc21 Overexpression In M Tubementioning
confidence: 99%
See 2 more Smart Citations
“…The results reported here support the notion that VapBC-1 (and TA modules in general) have evolved a number of mechanisms to maintain their activity and that their presence confers a significant advantage to the microorganism. Many studies have linked TA modules to the survival of bacterial pathogens in host tissues (7,(56)(57)(58)(59)(60). Achieving and maintaining persistence during an infection is central for both successfully evading the immune response and for nonspecific antibiotic tolerance, leading to a pathogen's survival of clinical therapy.…”
Section: Structural and Functional Studies Of Vapbc-1mentioning
confidence: 99%